Some New Integral Formulas Involving the Product of Multivariable Aleph Function, General Class of Srivastava Polynomials, M‐Series, and Hypergeometric Functions - Bhargava, Alok; Sharma, Komal Prasad; Suthar, D. L. (Journal of Mathematics, 2025)
Integral formulas play an important part in solving complicated scientific and technical problems. With this in mind, this study creates three essential formulas. These formulas include the product of the multivariable Aleph function, the general class of Srivastava’s polynomials, the M‐series, and hypergeometric functions. Some special cases are also presented to exhibit the approach through the simpler functions.